Analisis Pelaksanaan Sistem Prosedur Pengeluaran Kas Sekretariat DPRD Kota Magelang - Abim Aulya; Suci Nasehati Sunaningsih (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2021)
Cash disbursement is a series of funding incurred for activities that have benefits for agencies. The purpose of this study is to know the system of cash disbursement procedures at the Magelang City DPRD Secretariat Office. The object of this study is the Secretariat of the Magelang City DPRD. This research uses a descriptive method that aims to reveal facts, circumstances, phenomena that actually occur by comparing the systems and procedures for cash disbursements in the DPRD Secretariat with the concepts of effectiveness of cash disbursements that are theoretically studied. The obstacle faced during the cash disbursement process is the incomplete letter of accountability (SPJ) submitted for cash disbursement Keywords : System, State finance, Cash disbursemen